Environmental Performance Legitimacy and Market Price Dynamics : (A Comparative Study of the Coal Industry in Indonesia and Australia) - Farhan Nurmustaqim; Yessi Vionica Simanjuntak; Resi Ariyasa Qadri (Yayasan pendidikan dzurriyatul Quran, 2026)
Research objective: This study aims to analyze market responses to ESG disclosure in sustainability reports of coal companies in Indonesia and Australia within the framework of environmental legitimacy. Data were collected through documentation of ESG scores, sustainability reports, and stock price data within the H-5 to H+5 period. The analysis employed an interpretive qualitative approach by examining stock price movements and linking them to ESG disclosure contexts. The findings indicate that in Indonesia ESG functions as a mechanism to stabilize investor perception, while in Australia ESG acts as a stronger signal that is more rapidly reflected in the market. The results also show that market responses are contextual and influenced by institutional environments. Practical implication: This study highlights the importance of improving the quality and credibility of ESG disclosure to strengthen investor trust in the context of energy transition risks.